Intensity ratio of resonance lines as a diagnostic of initial conditions suitable for XUV laser action in recombining plasmas - Zhang, J; Key, M; Norreys, P; Tallents, G (1993)
The time varying ratio of intensities of resonance lines of H- and He-like ions in laser irradiated cylindrical fibre targets is analyzed using a hydro/atomic physics code. Correspondence between the ratio and gain on the Balmer α transition of H-like ions in the adiabatically cooling and recombining plasma is found. The line ratios and absorbed energies corresponding to maximum gains for carbon, oxygen and fluorine plasmas are calculated. A useful diagnostic method is proposed for infering the absorbed energies in the plasmas and for monitoring the production of plasmas which should give maximum gain during adiabatic expansion.